2021
DOI: 10.1016/j.jds.2020.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Computer-guided implant placement associated with computer-aided bone regeneration in the treatment of atrophied partially edentulous alveolar ridges: A proof-of-concept study

Abstract: Background/purpose The existing literature lacks information regarding the use of digital workflows during pre-surgical planning of implant rehabilitations in resorbed edentulous ridges. Thus, the aim was to evaluate the effectiveness of computer-guided implant placement and simultaneous computer-aided guided bone regeneration (GBR) in the treatment of atrophic posterior alveolar ridges. Materials and methods Partially edentulous patients requiring GBR simultaneously to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Although the implant type could theoretically diversely affect the outcomes in terms of accuracy, available studies investigating the effect of different implant macro designs have shown no significant difference in all parameters of accuracy (Kaewsiri et al, 2019; Schnutenhaus et al, 2021). With regard to the implant site studies on single implants have not shown any significant influence of the implant site on accuracy (Abduo & Lau, 2020; Kaewsiri et al, 2019) or the presence of bone augmentation (Kaewsiri et al, 2019; Poli et al, 2021). Nevertheless, in the case of fully edentulous patients, some authors have reported differences in the accuracy between the upper and lower jaw as well as posterior and anterior sites (Vercruyssen et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Although the implant type could theoretically diversely affect the outcomes in terms of accuracy, available studies investigating the effect of different implant macro designs have shown no significant difference in all parameters of accuracy (Kaewsiri et al, 2019; Schnutenhaus et al, 2021). With regard to the implant site studies on single implants have not shown any significant influence of the implant site on accuracy (Abduo & Lau, 2020; Kaewsiri et al, 2019) or the presence of bone augmentation (Kaewsiri et al, 2019; Poli et al, 2021). Nevertheless, in the case of fully edentulous patients, some authors have reported differences in the accuracy between the upper and lower jaw as well as posterior and anterior sites (Vercruyssen et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Among the implants in this study, 60% of the drop-out implants failed to obtain primary stability within the bony housing along with the fabricated guide. Therefore, even though guided surgery has become very predictable with the flapless approach, it cannot be applied in some patients, especially in those who have poor bone quality where primary stability cannot be obtained or requiring bone grafting due to a narrow ridge [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2021, Poli et al reported five patients for computer-guided implant placements with computer-aided guided bone regeneration using tooth-supported surgical guides stabilized by the residual dentition. They exhibited accurate results on implant position deviation of 0.73 ± 0.21 mm and 3.05 ± 1.22° at the implant head and long-axis, respectively [ 37 ]. Since that research performed bone graft after securing the primary stability of implants, however, their results was reported in areas with sufficient bone quality even if the amount of bone is insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…Dental implants are used in the replacement of missing teeth or provide retention and support for prostheses [ 9 , 10 ]. In particular, prosthetically guided approaches to implant insertion, fully digital, are currently a possible and recommended alternative [ 11 , 12 ]. Composition and roughness play an important role in implant-tissue interaction and osseointegration [ 13 – 15 ].…”
Section: Introductionmentioning
confidence: 99%